2004
DOI: 10.1128/iai.72.2.958-965.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Production of Systemic and Intralesional Gamma Interferon and Interleukin-10 in Nodular and Ulcerative Forms of Buruli Disease

Abstract: Buruli disease, caused by Mycobacterium ulcerans, is the third most important mycobacterial disease in humans besides tuberculosis and leprosy. We have compared systemic and intralesional cytokine production in patients presenting with a nodular form and a necrotizing, ulcerative form of the disease. Gamma interferon (IFN-␥) levels in response to whole M. ulcerans and Mycobacterium bovis BCG bacilli and in response to purified Ag85 protein from BCG were lower in peripheral blood mononuclear cells (PBMC) cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
94
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 35 publications
9
94
3
Order By: Relevance
“…Similarly, in vitro studies have demonstrated that subjects with M. ulcerans infection compared to exposed control subjects, have significantly lower production of IFN-γ and IL-12, with higher production of IL-4, IL-5, IL-6 and IL-10 in response to both M. ulcerans and BCG [20]. Similarly, RT-PCR analysis of cytokine gene expression in skin biopsies from patients with ulcerative BU, or analysis of the cytokine profile produced by their peripheral blood cells stimulated by specific immunodominant mycobacterial antigens, revealed lower IFN-γ production and higher IL-10 expression than in control BCG-vaccinated subjects or BU patients with nodular pre-ulcerative lesions [15]. Moreover, peripheral lymphocytes from patients before infection responded to in vitro stimulation with M. ulcerans by producing Th1 cytokines, but after ulcer development the response was shifted towards a predominantly Th2 cytokine profile [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in vitro studies have demonstrated that subjects with M. ulcerans infection compared to exposed control subjects, have significantly lower production of IFN-γ and IL-12, with higher production of IL-4, IL-5, IL-6 and IL-10 in response to both M. ulcerans and BCG [20]. Similarly, RT-PCR analysis of cytokine gene expression in skin biopsies from patients with ulcerative BU, or analysis of the cytokine profile produced by their peripheral blood cells stimulated by specific immunodominant mycobacterial antigens, revealed lower IFN-γ production and higher IL-10 expression than in control BCG-vaccinated subjects or BU patients with nodular pre-ulcerative lesions [15]. Moreover, peripheral lymphocytes from patients before infection responded to in vitro stimulation with M. ulcerans by producing Th1 cytokines, but after ulcer development the response was shifted towards a predominantly Th2 cytokine profile [21].…”
Section: Discussionmentioning
confidence: 99%
“…These effects of mycolactone on the immune system are important because mycobacterial infection is controlled essentially by Th1 cytokines and TNF-α , whereas Th2 cytokines (IL-4, IL-13) and anti-inflammatory cytokines, such as IL-10 and transforming growth factor (TGF)-β , have a detrimental effect on the control of bacterial proliferation [11][12][13][14]. Recent ex vivo studies using the reverse transcription-polymerase chain reaction (RT-PCR) to study skin biopsies and peripheral blood cells from patients with ulcerative BU lesions have demonstrated lower IFN-γ and higher IL-10 expression than in control Bacille Calmette-Guérin (CG)-vaccinated subjects or BU patients with nodular pre-ulcerative lesions [15]. However, to our knowledge, there are no published studies on the local, in vivo immunopathology in BU patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine studies on Buruli disease caused by Mycobacteria also showed that there was a difference in the cytokine response seen in ulcerative lesions when compared to nodular lesions. 19 All 4 normal skin biopsy samples displayed bands for IFN-γ but did not display bands for the other 3 cytokine mRNAs. A similar study carried out in Rajasthan detected low levels of mRNA for both IFN-γ (Th1) and IL-10 (Th2) by qPCR in control samples compared to CL lesions caused by L. tropica.…”
mentioning
confidence: 99%
“…According to a study done in India, a Th1 response is considered to influence a mild or self-curing form of the disease, whereas a Th2 response, which results in the production of IL-4 and IL-10, will influence the dissemination of the infection. 19 All the CL biopsy samples in this study were from localized lesions and the majority showing a Th1 cytokine response might have contributed to limit the dissemination of the disease. This study failed to detect a Th2 cytokine response which might have been due to low concentration of Th2 cytokines in the tissues and/or low sensitivity of the PCR.…”
mentioning
confidence: 99%
“…Gooding et al 12 reported expression of IL-4 and IL-10, among other cytokines, from BU patients while Prévot et al detected IL-10 and not IL-4. 13 Westenbrink et al on the other hand, detected neither IL-4 nor IL-10.…”
Section: Ulcerans Vaccine Targetsmentioning
confidence: 99%